2021 Korean Society of Gastrointestinal Endoscopy Clinical Practice Guidelines for Endoscopic Sedation - Hong Jun Park; Byung-Wook Kim; Jun Kyu Lee; Yehyun Park; Jin Myung Park; Jun Yong Bae; Seung Young Seo; Jae Min Lee; Jee Hyun Lee; Hyung Ku Chon; Jun-Won Chung; Hyun Ho Choi; et al. (Korean Society of Gastrointestinal Endoscopy, 2022)
Sedation can resolve anxiety and fear in patients undergoing endoscopy. The use of sedatives has increased in Korea. Appropriate sedation is a state in which the patient feels subjectively comfortable while maintaining the airway reflex for stable spontaneous breathing. The patient should maintain a state of consciousness to the extent that he or she can cooperate with the needs of the medical staff. Despite its benefits, endoscopic sedation has been associated with cardiopulmonary complications. Cardiopulmonary complications are usually temporary. Most patients recover without sequelae. However, they may progress to serious complications, such as cardiovascular collapse. Therefore, it is essential to screen high-risk patients before sedation and reduce complications by meticulous monitoring. Additionally, physicians should be familiar with the management of emergencies. The first Korean clinical practice guideline for endoscopic sedation was developed based on previous worldwide guidelines for endoscopic sedation using an adaptation process. The guideline consists of nine recommendations based on a critical review of currently available data and expert consensus when the guideline was drafted. These guidelines should provide clinicians, nurses, medical school students, and policy makers with information on how to perform endoscopic sedation with minimal risk.